PERSEPSI PETANI PADI TERHADAP KEGIATAN PENYULUHAN PERTANIAN DI DESA SUKARAMI KELURAHAN TABA PENANJUNG KABUPATEN BENGKULU TENGAH - Mindo Marsaulina T; Herlina -; Yossie Yum (UNIVED Press, Universitas Dehasen Bengkulu, 2014)
Agricultural development is an important and integral part of national development. It is evident from the self-sufficiency of rice in 1982. The success of agricultural development is inseparable from agricultural extension activities as a social innovation that aims to change the behavior of people (farmers) to always be ready and able to master and apply each alternative innovations that can be used to improve farm productivity (Mardikanto, 1991). Extension activities can be run if the farmer who supports that goal by holding counseling can be delivered and realized. In this study, researchers wanted to examine the perceptions of paddy farmers towards agricultural extension activities in the Sukarami village, Taba Penanjung, Middle of Bengkulu Regency. The research was conducted in June - July 2013 in Sukarami village, Taba Penanjung, of Middle Bengkulu regency. Sampling was performed with a standard deviation formula involving 36 people from the 182 sample respondents. Necessary data were taken from two sources namely primary data and secondary data. Primary data is data obtained directly from respondents by conducting interviews based on questionnaires that have been prepared. Secondary data were taken from previous data like from the village office and others agencies associated with this research. Based on the research results, it can be concluded that the perception of farmers on agricultural extension activities are good because it can increase the farmers knowledge, skills, motivation and farm productivity.Keywords : Perceptions, Farmers, Agricultural Extension.